Membangun Problem-solving Skill di Tempat Kerja melalui Pembentukan Keterampilan Literasi Sains: Sebuah Tinjauan Literatur - Fahru Riza; Yoto Yoto; Didik Nurhadi (Jurnal Taman Vokasi, 2025)
Science literacy plays an important role in shaping Problem-solving Skills in the workplace, especially in the face of increasingly complex industry challenges. This study uses the Narrative Literature Review (NLR) approach to explore the relationship between science literacy and problem-solving skills and identify effective approaches in improving these competencies. Problem-Based Learning (PBL) (PBL) and Root Cause Analysis (RCA) are proven methods to improve critical thinking, analytical, and data-driven decision-making skills in the work environment. The results of the study showed that workers with better science literacy have higher abilities to analyze problems, develop innovative solutions, and optimize the production process. In addition, strategies to increase science literacy through problem-based training, team collaboration, and employee empowerment have proven to be effective in supporting the strengthening  of Problem-solving Skills. Evaluation of training programs is necessary to ensure their effectiveness in meeting industry needs. Thus, the integration of science literacy in vocational education and industrial training programs is a strategic step in preparing an adaptive, innovative, and competitive workforce. This study provides recommendations for the world of education and industry in developing a science literacy-based curriculum to increase the competitiveness of the workforce in the digital era.